Development of Media for Introduction and Prevention of Covid-19 Based on Role Playing Game for Elementary School - Saputri, Fiqih Hana; Ferawati, Ferawati (JURNAL SISFOTEK GLOBAL, 2021)
This research aim to create game based on role playing game for introduction and prevention of Covid-19 in elementary school. In education, technology is needed to support the learning process, especially during the current Covid-19 pandemic, which requires students to study at home. Of course, in online learning between students and teachers, liaison media is needed to carry out the learning process, one of which is the introduction and prevention of Covid-19, which many children still do not understand. Therefore, games are needed to open and prevent Covid-19 from facilitating information for students in recognizing and knowing the prevention of Covid-19. The game is designed using Role Playing Game Maker MV in which there are characters. The game contains six grade levels. In each game, there are questions that students must answer to move up to the next grade level. Based on the questionnaire results using the Software Quality Assurance metric, the Monster Corona game has a value obtained from the results of the questionnaire, which is 82.6. At the same time, the value of the feasibility of the Monster Corona game quality is 80. The value obtained from the questionnaire is 2.6 different, and it is considered that the Monster Corona game is suitable for use. This game can be used as a student resource for the introduction and prevention of Covid-19.